Effects of removal of young leaves and cytokinin on inflorescence development and bract enlargement in bougainvillea glabra var. "Elizabeth Angus" - Moneruzzaman, K.M.; Amru, N.B.; Sani, W.; Saifuddin, M.; Normaniza, Osman; Hossain, A.B.M.S. (Southern Cross Publishing, 2010)
A study was carried out to investigate the effects of removal of young leaves and different concentrations of cytokinin on inflorescence and bract quality development of Bougainvillea. Selected horticultural parameters were monitored at three days interval during the experimental period, using different concentrations of cytokinin with defoliation of young leaf. Results revealed that de-foliation with or without citokinin greatly increased the amount of assimilate accumulated at the reproductive shoot tip thus reduced vegetative growth but promotes inflorescence development. It was observed that 50mg/L cytokinin with defoliated twig produced highest number of bract, excellent blooming rate, enlarging the bract length and increase the bract longevity from other treatments and control. Furthermore, 50mg/L cytokinin plus defoliated branch produced the highest chlorophyll fluorescence and quantum yield. On the other hand, cytokinin 100mg/L treatment in defoliated plant increased the weight of individual bract and bracts including flower. Control treatment increased the stem elongation and enhanced the vegetative growth only. From this study, it can be concluded that defoliation of young leaf and cytokinin 50mg/L treatment enhanced inflorescence development and improve the quality of Bougainvillea bracts.